PENGARUH KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - Jullimursyida Ganto; Muammar Khadafi; Wahyuddin Albra; Gazali Syamni (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
The objective of this research is to determine the significant effects of financial performance of manufacturing industries to stock return in Indonesia Stock Exchange. The secondary data was used with the multiple linear regression analysis. The results show that earning per share and price earning ratio have positive and significantly effects to stock return. This research also finds retum on equity and price to book value does not have any significant effects to stock return. The finding of this research suggests that to include all of the fisting companies for futher research.Keywords: earning per share, price earning ratio, return on equity, price to book value, stock return, manufacturing industries, Indonesia stock exchange.